Promoting Student’s Well-being in Islamic Education: Teacher Strategies and Future Prospects - Hasanah, Uswatun; Pratama, Yoga Anjas; Ningrum, Ayu Reza; Nuraini, Nuha (IJECA (International Journal of Education and Curriculum Application), 2023)
Islamic education has been modernized in every respect to meet the demands of the day, yet the results have fallen short of expectations. One reason is that learning activities place less emphasis on factors of student well-being. As a result, the purpose of this study is to increase student well-being in Islamic education, with an emphasis on teacher strategies and future possibilities. This study is field research, the research informants were 8 Islamic teachers from five Islamic educational institutions in Bandar Lampung who were determined using a purposive sampling technique. According to the study, student well-being is vital to successful learning. Thus numerous parties, particularly teachers, play a role in fostering student well-being. Personal consultation, sharing sessions, fostering openness and trust, not judging students and carefully listening to them, being careful with language and always giving up space for inquiries, and teaching how to seek help are some of the teacher strategies that can be implemented. It can be concluded, that future teachers can seek to create student well-being by implementing strategies that address students' needs in four dimensions: having, loving, being, and health.